Tourist Engagement in the Digital Age: The Catalytic Role of Content Marketing for Sustainable Destination Promotion - FAREH MORAD; IDRISSI KHADIJA (International Journal of Scientific Research and Innovative Studies, 2025)
This research article aims to assess the impact of content marketing on promoting sustainable tourism for a specific destination. We will examine how the creation and dissemination of digital content (photos, videos, social networks) influence tourists' perceptions and encourage them to adopt more responsible behaviors. The methodology will combine a literature review on both concepts (content marketing and sustainable tourism) with an empirical case study of the Moroccan city destination Agadir. The study proposes a quantitative approach based on an online and on-site questionnaire administered to a large sample of tourists who have stayed in Agadir. The analysis of the data collected using statistical techniques will measure the correlation between exposure to promotional digital content and tourists' propensity to engage in sustainable tourism activities. The expected results should make it possible to identify strategic recommendations for the Regional Tourism Council (CRT) of Agadir, the Moroccan National Tourism Office (ONMT) and private stakeholders, in order to optimize their communication campaigns and strengthen the image of the city as a destination that respects the environment and local culture. Keywords : Content Marketing, Sustainable Tourism, Tourist Destination, Engagement, Tourists. Received Date: July 19, 2025 Accepted Date: August 11, 2025 Published Date: August 30, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/410